Leading the rebirth of the rural obstetrician. Issue 11 (15th December 2014) - Campbell, Alison M; Brown, James; Simon, David R; Young, Sari; Kinsman, Leigh
Abstract: Objectives : To understand the factors influencing the decisions of rural general practitioners and GP registrars to practise obstetrics, and to understand the impact on these decisions of an innovative obstetric training and support program in the Gippsland region of Victoria. Design, setting and participants: Qualitative approach using semistructured interviews conducted in July and August 2013 and inductive content analysis. Participants were identified from training records over the previous 5 years for the Gippsland GP obstetric training and support program. Two questions were posed during interviews: What challenges face rural GPs in practising obstetrics? What impact has the Gippsland GP obstetric program had on GP obstetric career decisions? Results: Of 60 people invited to participate, 22 agreed. Interviews ranged in duration from 40 to 90 minutes. The major themes that emerged on the challenges facing rural GPs in practising obstetrics were isolation, work–life balance and safety. The major themes that emerged on the impact of the Gippsland GP obstetric program were professional support, structured training and effective leadership. Conclusion: Rural GP obstetricians are challenged by isolation, the impact of their job on work–life balance, and safety. The support, training and leadership offered by the Gippsland expanded obstetric training program helped doctors to deal with these challenges. The Gippsland model of training offers a template for GP obstetric procedural training programs for other rural settings.